2003
DOI: 10.1002/dvdy.10327
|View full text |Cite
|
Sign up to set email alerts
|

Chronological gene expression of ADAMs during testicular development: Prespermatogonia (gonocytes) express fertilin β (ADAM2)

Abstract: Immediately after birth, primordial germinal cell-derived prespermatogonia (PSG), located in the center of the testicular cords, migrate between adjacent Sertoli cells to establish contact with the cord basal lamina. PSG migration suggests continued assembly and disassembly of cell-cell contacts by a molecular mechanism that may involve integrins and their ligands, the disintegrin domain of spermatogenic cell-specific plasma membrane proteins called ADAMs. We have analyzed the temporal gene expression of selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…ADAM5 is part of a large family of transmembrane proteins that can serve as integrin ligands. While it is detected in the embryonic prospermatogonia [55], it is also expressed during spermatogenesis and appears on the mature sperm surface after undergoing proteolytic processing in the epididymis [56]. These three genes have X box motifs with strong binding affinities and each shows marked up-regulation in developing testes at a point coincident with early entry into pachytene [30].…”
Section: Discussionmentioning
confidence: 99%
“…ADAM5 is part of a large family of transmembrane proteins that can serve as integrin ligands. While it is detected in the embryonic prospermatogonia [55], it is also expressed during spermatogenesis and appears on the mature sperm surface after undergoing proteolytic processing in the epididymis [56]. These three genes have X box motifs with strong binding affinities and each shows marked up-regulation in developing testes at a point coincident with early entry into pachytene [30].…”
Section: Discussionmentioning
confidence: 99%
“…ADAM 1 and ADAM 2 were originally found at the surface of sperm and believed to play a role in sperm‐egg interaction (Chen and Sampson,1999), although the generation of ADAM2 and β1 KO mice subsequently showed that these proteins were not required for gamete fusion (Cho et al,2000; He et al,2003). ADAM 1 and ADAM 2 are not expressed in PGCs and appear at dpp1 (ADAM1) and dpp2 (ADAM2) mouse gonocytes (Rosselot,2003). Integrins α3β1 and α6β1 bind laminin, a major component of the seminiferous tubule basement membrane, and they play a critical role in Sertoli‐germ cell interactions as well as germ cell survival (Siu and Cheng,2004a,b).…”
Section: What Regulate Gonocyte Functions?mentioning
confidence: 99%
“…Sections were stained for 5 min with 5% uranyl acetate in deionized water and examined using a JEM-100CX transmission electron microscope operated at an accelerating voltage of 60 kV. Sections (1 mm-thick) of Lowicryl-embedded tissue were immunoreacted with ODF2-specific antibody, bound antibody visualized with anti-rabbit IgG-fluorescein isothiocyanate (working dilution: 1:200), stained with propidium iodide using a reported protocol (Rosselot et al, 2003) and observed by episcopic fluorescence microscopy.…”
Section: Immunocytochemical Localization Ofmentioning
confidence: 99%